Development of a Scaffolding Learning Strategy to Increase Student Learning Independence at SMK Muhammadiyah 2 Pekanbaru - Cynthia Rahmi; Suarman Suarman; Henny Indrawati (Journal of Education and Learning Research, 2024)
This research aims to develop learning strategy scaffolding to increase student learning independence. Research uses methods Research and Development (R&D) ADDIE development model. This research was carried out at SMK Muhammadiyah 2 Pekanbaru on Fixed Assets material. Data was collected through 3 learning strategy experts and 2 material experts. Data analysis uses quantitative descriptive. The research results show that the strategy development instruments and materials created are valid and suitable for use in research. The results of product trials show that the development of learning strategy scaffolding effectively increasing student learning independence. Results pretest Learning independence shows that 55.18% of students are in the low category. Then post test shows 41.37% of students have high learning independence. Student learning outcomes also showed an increase and student responses showed that 59% of students chose learning strategy scaffolding is in the good and useful category. Thus it can be said that the development of learning strategy scaffolding increase student learning independence.